Insomnia of students following the lifting of COVID-19 restrictions in China: Prevalence, influencing factors, and associations with depression, anxiety, and PTSD - Zhang, Hang; Yin, Li; Wang, Cong; Liu, Yi-Hao; Yang, Yi-Yue; Zhou, Lie; Jin, Hui; Xiao, Yun; Wen, Yang; Ahmad, Jawad; Cai, Jia; Wang, Yu; et al. (Frontiers in Psychiatry, 2025)
IntroductionInsomnia has emerged as a major concern among youth following the lifting of coronavirus disease 2019 (COVID-19) restrictions in China. This study aimed to explore the prevalence and influencing factors of insomnia, as well as its associations with mental health, in young students during this period.MethodsA cross-sectional survey was conducted among 82,873 students in Sichuan Province, China, using a self-designed questionnaire and standardized assessment tools. Chi-square tests, ANOVA with post-hoc test analyses, and logistic regression were employed to identify the prevalence and influencing factors of insomnia and its associations with mental health.ResultsA total of 28,178 (34.0%) students reported insomnia. Self-reported history of mental disorders, neglectful parenting, and initiating alcohol consumption during the pandemic were associated with higher odds of insomnia, whereas satisfaction with the academy, full recovery of daily routines, greatly improved family relationships, no change in friendships, and higher maternal education were associated with lower odds of insomnia (p < 0.001). Severe insomnia was strongly associated with depression, anxiety, and posttraumatic stress disorder (PTSD; ORs: 17.55, 3.35, and 17.45, respectively). Interaction effects were observed between mild to moderate insomnia and COVID-19 infection on depression, anxiety, and PTSD.ConclusionFollowing the lifting of COVID-19 restrictions, insomnia remained prevalent among young Chinese students. Preexisting self-reported mental disorders, neglectful parenting, and pandemic-related maladaptive behaviors increase the risk of insomnia, whereas positive lifestyle adjustments, stable relationships, and higher maternal education appear protective. A significant association was observed between insomnia severity and symptoms of depression, anxiety, and PTSD. These findings highlight the persistent links among social, behavioral, and demographic factors, sleep, and mental health, emphasizing the importance of addressing sleep disturbances after the public health crisis.